An update on the amphibian assemblage of the Ukaguru Mountains, Tanzania, with the description of a new giant Arthroleptis species (Amphibia: Anura) - John Lyakurwa; H. Christoph Liedtke; Pius Mollel; Gabriela B. Bittencourt-Silva; Robert Jehle; Simon P. Loader; Wilirk Ngalason (Systematics and Biodiversity, 2025)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

A juvenile Tristan albatross (Diomedea dabbenena) on land at the Crozet Islands - Alexander L. Bond; Christopher Taylor; David Kinchin-Smith; Derren Fox; Emma Witcutt; Peter G. Ryan; Simon P. Loader; Henri Weimerskirch (Polar Biology, 2021)
Albatrosses and other seabirds are generally highly philopatric, returning to natal colonies when they achieve breeding age. This is not universal, however, and cases of extraordinary vagrancy are rare. The Tristan Albatross ( Diomedea dabbenena ) breeds on Gough Island in the South Atlantic Ocean, with a small population on Inaccessible Island, Tristan da Cunha, ca 380 km away. In 2015, we observed an adult male albatross in Gonydale, Gough Island, which had been ringed on Ile de la Possession, Crozet Islands in 2009 when it was assumed to be an immature Wandering Albatross ( D. exulans ). We sequenced 1109 bp of the cytochrome b mitochondrial gene from this bird, and confirmed it to be a Tristan Albatross, meaning its presence on Crozet 6 years previous, and nearly 5000 km away, was a case of prospecting behaviour in a heterospecific colony. Given the challenges in identifying immature Diomedea albatrosses, such dispersal events may be more common than thought previously.

Causes and analytical impacts of missing data in RADseq phylogenetics: Insights from an African frog ( Afrixalus ) - Marco Crotti; Christopher D. Barratt; Simon P. Loader; David J. Gower; Jeffrey W. Streicher (Zoologica Scripta, 2019)
Restriction site‐associated DNA sequencing (RADseq) has emerged as a useful tool in systematics and population genomics. A common feature of RADseq data sets is that they contain missing data that arise from multiple sources including genealogical sampling bias, assembly methodology and sequencing error. Many RADseq studies have demonstrated that allowing sites (single nucleotide polymorphisms, SNPs) with missing data can increase support for phylogenetic hypotheses. Two non‐mutually exclusive explanations for this observation are that (a) larger data sets contain more phylogenetic information; and (b) excluding missing data disproportionally removes sites with the highest mutation rates, causing the exclusion of characters that are likely variable and informative. Using a RADseq data set derived from the East African banana frog, Afrixalus fornasini (up to 1.1 million SNPs), we found that missing data thresholds were positively correlated with the proportion of parsimony‐informative sites and mean branch support. Using three proxies for estimating site‐specific rate, we found that the most conservative missing data strategies excluded rapidly evolving sites, with four‐state sites present only when allowing ≥60% missing data per SNP. Topological similarity among estimated phylogenies was highest for the data sets with ≥60% missing data per SNP. Our results suggest that several desirable phylogenetic qualities were observed when allowing ≥60% missing data per SNP. However, at the highest missing data thresholds (80% and 90% missing data per SNP), we observed differences in performance between high‐ and mixed‐weight DNA extraction samples, which may indicate there are trade‐offs to consider when using degraded genomic template with RADseq protocols.

Vanishing refuge? Testing the forest refuge hypothesis in coastal East Africa using genome‐wide sequence data for seven amphibians - Christopher D. Barratt; Beryl A. Bwong; Robert Jehle; H. Christoph Liedtke; Peter Nagel; Renske E. Onstein; Daniel M. Portik; Jeffrey W. Streicher; Simon P. Loader (Molecular Ecology, 2018)
High‐throughput sequencing data have greatly improved our ability to understand the processes that contribute to current biodiversity patterns. The “vanishing refuge” diversification model is speculated for the coastal forests of eastern Africa, whereby some taxa have persisted and diversified between forest refugia, while others have switched to becoming generalists also present in non‐forest habitats. Complex arrangements of geographical barriers (hydrology and topography) and ecological gradients between forest and non‐forest habitats may have further influenced the region's biodiversity, but elucidation of general diversification processes has been limited by lack of suitable data. Here, we explicitly test alternative diversification modes in the coastal forests using genome‐wide single nucleotide polymorphisms, mtDNA, spatial and environmental data for three forest ( Arthroleptis xenodactyloides , Leptopelis flavomaculatus and Afrixalus sylvaticus ) and four generalist ( Afrixalus fornasini , A. delicatus , Leptopelis concolor and Leptopelis argenteus ) amphibians. Multiple analyses provide insight about divergence times, spatial population structure, dispersal barriers, environmental stability and demographic history. We reveal highly congruent intra‐specific diversity and population structure across taxa, with most divergences occurring during the late Pliocene and Pleistocene. Although stability models support the existence of some forest refugia, dispersal barriers and demographic models point towards idiosyncratic diversification modes across taxa. We identify a consistent role for riverine barriers in the diversification of generalist taxa, but mechanisms of diversification are more complex for forest taxa and potentially include topographical barriers, forest refugia and ecological gradients. Our work demonstrates the complexity of diversification processes in this region, which vary between forest and generalist taxa, but also for ecologically similar species with shared population boundaries.

Persistence and stability of Eastern Afromontane forests: evidence from brevicipitid frogs - Simon P. Loader; F. Sara Ceccarelli; Michele Menegon; Kim M. Howell; Roman Kassahun; Abebe A. Mengistu; Samy A. Saber; Fikirte Gebresenbet; Rafael de Sá; Tim R. B. Davenport; Joanna G. Larson; Hendrik Müller; et al. (Journal of Biogeography, 2014)
Aim The persistence and stability of habitats through time are considered predictors of high levels of biodiversity in some environments. Long‐term habitat persistence and stability may explain the species‐rich, endemic forest fauna and flora of the Eastern Afromontane Biodiversity Region ( EABR ). Using complementary phylogenetic and biogeographical approaches, we examine evolutionary patterns in EABR brevicipitid frogs. Using these data, we test whether brevicipitid history reflects patterns of long‐term forest persistence and/or stability across the EABR . Location East Africa. Methods A dated phylogeny for brevicipitids was constructed using two nuclear and three mitochondrial markers. Alternative diversification models were used to determine signal for constant or varying net diversification rates. Using our dated tree, we identified areas of high phylogenetic diversity ( PD ), and inferred ancestral areas using likelihood and Bayesian approaches. Results Brevicipitids have a long history, with generic diversification among extant lineages pre‐dating the Oligocene (> 33 Ma). Ancestral‐area reconstructions indicate the presence of brevicipitids in the EABR since the Oligocene, and support a scenario of palaeoendemics surviving in EABR refugia. Ancestral‐area reconstructions indicate that the central Eastern Arc Mountains ( EAM ) formed the initial centre of diversification of forest brevicipitids. Measures of PD show that diversity varies across the EABR but is highest in the EAM . Constant net diversification rate in brevicipitids is a significantly better fit than alternative, rate‐variable models. Main conclusions The degree of persistence of forest habitats appears to be a contributing factor to the varying levels of diversity across the EABR in brevicipitids (and other organisms). In contrast to the Southern Highlands and Ethiopian Bale Mountains, the EAM stands out as an area that enabled the constant accumulation of brevicipitid species over a long period of time.

Testate amoebae as a proxy for reconstructing Holocene water table dynamics in southern Patagonian peat bogs - SIMON VAN BELLEN; DMITRI MAUQUOY; RICHARD J. PAYNE; THOMAS P. ROLAND; TIM J. DALEY; PAUL D. M. HUGHES; NEIL J. LOADER; F. ALAYNE STREET‐PERROTT; EMMA M. RICE; VERÓNICA A. PANCOTTO (Journal of Quaternary Science, 2014)
Testate amoebae are abundant and diverse in Sphagnum peat bogs and have been used extensively as indicators of past water table depths. Although these unicellular protists are widely dispersed with globally similar hydrological preferences, regional variations in communities demand region‐specific transfer functions. Here we present the first transfer function for southern Patagonian bogs, based on 154 surface samples obtained from transects in five bogs sampled in 2012 and 2013. Significant variance was explained by pH, electrical conductivity and, in particular, water table depth. Transfer functions for water table were constructed using weighted averaging and evaluated by cross‐validation and independent test sets. The optimal transfer function has predictive ability, but relatively high prediction errors given the wide range in sampled water tables. The use of independent test sets, as well as cross‐validation, allows a more rigorous assessment of model performance than most previous studies. For a subset of locations we compare surface and subsurface samples to demonstrate significant differences in community composition, possibly due to vertical zonation. Our results provide the first quantification of hydrological optima and tolerances for several rare species, which may include Southern Hemisphere endemics and pave the way for palaeohydrological reconstructions in southern Patagonian bogs.

Characterisation of nine microsatellite loci in the caecilian amphibian Boulengerula uluguruensis (Gymnophiona), and their cross-species utility in three congeneric species - Christopher D. Barratt; Gavin J. Horsburgh; Deborah A. Dawson; David J. Gower; Mark Wilkinson; Simon P. Loader; Robert Jehle (Conservation Genetics Resources, 2012)